2004
DOI: 10.2165/00126839-200405050-00004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of D-003, a Mixture of Very High Molecular Weight Aliphatic Acids, on Prednisolone-Induced Osteoporosis in Sprague-Dawley Rats

Abstract: D-003 (5, 25 and 200 mg/kg) prevented trabecular bone loss and femoral neck osteonecrosis induced with prednisolone in Sprague Dawley rats, also increasing osteoblast surface and reducing bone resorption parameters. These results suggest that D-003 could be useful for managing corticosteroid-induced osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…GC administration has been shown to induce loss of the cancellous BV/TV, Tb N, and Tb Th of the lumbar spine in rats and also loss of the three-dimensional cancellous BV/TV and Tb Th, an increase in the trabecular bone pattern factor in the lumbar spine of minipigs (15)(16)(17)(18)(19)(20)(21). GC-induced cancellous osteopenia has been shown to be associated with decreased bone formation and increased bone resorption, and the key histological Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GC administration has been shown to induce loss of the cancellous BV/TV, Tb N, and Tb Th of the lumbar spine in rats and also loss of the three-dimensional cancellous BV/TV and Tb Th, an increase in the trabecular bone pattern factor in the lumbar spine of minipigs (15)(16)(17)(18)(19)(20)(21). GC-induced cancellous osteopenia has been shown to be associated with decreased bone formation and increased bone resorption, and the key histological Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that GC induces the loss of cancellous BV/TV, Tb N, and Tb Th, decreases longitudinal bone growth and femoral bone length, and reduces the mechanical strength of the lumbar spine [5,6,[15][16][17]22]. GC-induced osteopenia has been associated with decreased bone formation, with the effects on bone resorption in terms of osteoclastic activity being inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…GC administration has been shown to induce a loss in 2D cancellous BV/TV, Tb N, and Tb Th, coupled with deterioration of the mechanical properties of the lumbar spine in rats (17)(18)(19)(20)(21)(22); It has also been shown to induce a loss in 3D cancellous BV/TV and Tb Th, with an increase in trabecular bone pattern factor and deterioration of the mechanical properties of the lumbar spine in minipigs ( 23 ). However, long-term administration of GCs may be needed before 2D and 3D cancellous bone structures are modified in animals ( 24 ).…”
Section: Discussionmentioning
confidence: 99%